The Impact Of Online Game Addiction On Financial Behavior (Case Study Of Gen Z In Sub Urban Islamic Economic Perspective) - Alifiansyah, Muhammad Hanif; Fauzia, Ika Yunia (Journal of Entrepreneurship & Business, 2025)
Purpose: The purpose of this study is to examine, from an Islamic economic standpoint, the effects of online game addiction on the financial behavior of Generation Z in suburban regions. This study is novel because it combines behavioral finance, digital consumption patterns, and Islamic ethical values to investigate how digital-native youth handle their finances after engaging in prolonged gaming. This has not been extensively studied in prior research, especially in the context of Islamic economics. Method: This study used a qualitative case study methodology. 13 members of Generation Z living in suburban Sidoarjo who fit the description of online gamers who play for more than five hours every day and have dealt with in-game purchases made up the unit of analysis. Triangulation was used to ensure the validity of the data. Islamic financial behavior theories served as the foundation for the conceptual framework, and descriptive qualitative analysis with phases of data reduction, presentation, and conclusion drawing was the analytical methodology employed. Result: The findings reveal that online game addiction significantly influences impulsive and unplanned digital spending habits among Gen Z. While many informants are aware of Islamic financial principles, their application in daily financial decisions remains minimal. However, some informants have begun adopting more responsible behaviors. This study contributes to the growing discourse on Islamic behavioral finance and recommends the development of contextualized Islamic financial literacy models for digital-native generations. Future research may expand into quantitative assessments or comparative studies between urban and rural youth